Morphological evidence uncovers a new species of Goniurosaurus (Squamata: Eublepharidae) from the Hainan Island, China - Zhou, Run-Bang; Wang, Ning; Chen, Bei; Liang, Bin (Zootaxa, 2018)
A new species of the genus Goniurosaurus, G. zhoui sp. nov., is described based on specimens collected from karst areas in Hainan Island, China. Quantitative comparison of morphological traits and egg size with two known endemic species in Hainan Island and other known congeners confirmed the distinctiveness of G. zhoui sp. nov., which has a moderate size with a snout-vent length of 93.4–97.4 mm; light purple-brown dorsal ground color in adults; a posteriorly protracted nuchal loop on nape; four faint, purple-gray body bands bearing dark purple spots between and on them; eight nasal scales surrounding nares; single internasal; 49–62 eyelid fringe scales; 130–140 scales around midbody; 11 granular scales surrounding the dorsal tubercles; 36–38 precloacal pores in males (absent in females); claws sheathed by four scales, two lateral scales long and curved. We provide the first data on the natural history of the new species and an expanded key to Goniurosaurus species on Hainan Island and the adjacent mainland. The discovery of the new species facilitates our understanding of the speciation process on continental islands.